Development of transplanting manipulator for hydroponic leafy vegetables - Li, Bo; Gu, Song; Chu, Qi; Yang, Yanli; Xie, Zhongjian; Fan, Kaijun; Liu, Xiaogeng (International Journal of Agricultural and Biological Engineering, 2019)
The production of hydroponic leafy vegetable plug-seedlings uses coco-peat as culture substrate in South China. Coco-peat has lowered density than peat-moss, and the friction between substrate block and pickup tool is small. So, it is hard to pick up in mechanism transplantation. In order to increase the friction, the existing transplanting manipulator had relatively complex structures. To simplify the structure of transplanting manipulator and improve the stability of picking up substrate block, four stainless steel fingers with rectangular cross-section were used in this research. A vertical driving was used to realize the coupling effect that could insert and shrink at the same time, by applying different combination of constraints to the steel fingers. This could increase friction between the steel fingers and the substrate block, and then enhance the stability of the substrate block. Different combinations of constraints were applied to the rectangular stainless steel fingers (3 mm×0.8 mm). The working videos of steel fingers were taken by high-speed photography. High-speed motioned analysis software was used to acquire and analyze traces of steel fingers movements. When the length which top end of the steel fingers moved outward (M) is equal to 1.5 mm, the length which guiding part widened (N) is equal to 1 mm, the shrinking distance of steel fingers is 4.2 mm. In this research, 16-day hydroponic leafy vegetable plug-seedlings were used for performance, which cultivated with coco-peat substrate with the moisture in the substrate at 81%. The transplanting manipulator was attached to a Denso robotic arm to conduct transplanting performance test. When the shrinking distance of steel fingers increased from 0 mm to 3.2 mm and the inserting angle decreased from 80° to 77°, the lifting force of substrate block increased by 118% from 1.45 N to 3.16 N. However, excessive shrinkage stirred the substrate block, which would reduce the friction between the substrate block and pickup parts and lowered the lifting force of pickup part in the substrate block. The experimental results also demonstrated that when the shrinking distance of the steel fingers reached 3.2 mm and the root distribution rate reached 46%, the success rate of transplantation was 80%. When the leafy vegetable plug-seedlings root distribution rate reached 92%, the success rate of transplantation was 96.67%. The degree of root distribution rate was positively correlated with the transplantation success rate. Therefore, in order to ensure an acceptable success rate of transplantation, the root distribution rate of leafy vegetable plug-seedlings should be at least 90%. This study provides a technical reference for developing simplified transplanting manipulator that can be used to transplant the hydroponic leafy vegetable plug-seedlings with coco-peat as the culture substrate. Keywords: transplanting robot, transplant manipulator, steel fingers, hydroponic leafy vegetable plug-seedlings, high-speed photography, guidance constraints, shrinkage DOI: 10.25165/j.ijabe.20191206.5050 Citation: Li B, Gu S, Chu Q, Yang Y L, Xie Z J, Fan K J, et al. Development of transplanting manipulator for hydroponic leafy vegetables. Int J Agric & Biol Eng, 2019; 12(6): 38–44.